Inhibition of norovirus 3CL protease by bisulfite adducts of transition state inhibitors - Mandadapu, Sivakoteswara Rao; Gunnam, Mallikarjuna Reddy; Tiew, Kok-Chuan; Uy, Roxanne Adeline Z.; Prior, Allan M.; Alliston, Kevin R.; Hua, Duy H.; Kim, Yunjeong; Chang, Kyeong-Ok; Groutas, William C. (My University, 2013)
Noroviruses are the most common cause of acute viral gastroenteritis, accounting for >21 million cases annually in the U.S. alone. Norovirus infections constitute an important health problem for which there are no specific antiviral therapeutics or vaccines. In this study, a series of bisulfite adducts derived from representative transition state inhibitors (dipeptidyl aldehydes and α-ketoamides) was synthesized and shown to exhibit anti-norovirus activity in a cell-based replicon system. The ED[subscript 50] of the most effective inhibitor was 60 nM. This study demonstrates for the first time the utilization of bisulfite adducts of transition state inhibitors in the inhibition of norovirus 3CL protease in vitro and in a cell-based replicon system. The approach described herein can be extended to the synthesis of the bisulfite adducts of other classes of transition state inhibitors of serine and cysteine proteases, such as α-ketoheterocycles, α-ketoesters, and others.
Keywords: Norovirus 3CL protease; Bisulfite salt adducts; Transition state inhibitors